Death before wicket : a Phryne Fisher mystery - Greenwood, Kerry (Greenwood, Kerry. Phryne Fisher mystery, 2018)
The sassy Phryne Fisher comes to Sydney! This is the 10th Phryne Fisher mystery. Phryne Fisher has plans for her Sydney sojourn, but they begin to go awry when Phryne's maid discovers that her respectable sister Joan has left her family for the murky nightlife on the Cross...and then postponed again because Phyrne is definitely not the woman to say 'no' when two delightful young men are on their knees, begging for her help in finding their friend innocent of theft. It all sounds simple enough as Phryne sets investigations into motion. But when greed and fear are the motivating factors, people become ruthless and Phyrne quickly finds herself enmeshed in blackmail, secrets, lies and the dangerous influences of deep magic.